NEUTRON DOSIMETRY AT ONTARIO POWER GENERATION: CALIBRATION FACTORS FOR THE SNOOPY - NP-100 NEUTRON REM-METER - Moscu, Diana F. (My University, 2005)
Within the CANDU workplace only a small fraction of workers are exposed to neu tron radiation. For these individuals, roughly 4.5% of the total radiation equivalent dose is the result of exposure to neutrons. When this value is considered across all workers within the CANDU workplace only 0.25% of the total radiation equivalent dose is the result of exposure to neutrons. Neutron dosimetry at Ontario Power Generation (OPG) is governed by the Canadian Nuclear Safety Commission (CNSC) through Regulatory Stan dard S-106, an Atomic Energy Control Board (AECB) document. The dosimetry program includes both direct and indirect dosimetry methods. For direct dosimetry, a moderator based neutron rem-meter is used to measure both ambient dose equivalent and ambient dose equivalent rates. One method of indirect dosimetry employs maps of neutron dose rates, measured using a moderator-based neutron rem-meter, along with the time spent in a particular area to calculate the equivalent dose. The current neutron rem-meter em ployed is the NP-100, previously the NP-2, manufactured by Canberra Industries Incor porated. These detectors are both known as “SNOOPY”. The rem-meters used at Ontario Power Generation are calibrated by the National Research Council of Canada (NRCC), Institute for National Measurement Standards. The result of the calibration is a factor which relates the neutron count rate to the ambient dose equivalent rate, using a stan dard Am-Be neutron source. Using the measurements presented in a CANDU Owner’s Group Inc. Technical Note, “Capability maintenance in Neutron Dosimetry 2003/04 - Performance-testing a Neutron Survey Meter” (Nunes and Surette, 2004) readings from the rem-meter for six different neutron fields—in six source-detector orientations—were used, to determine a calibration factor for each of these sources. The calibration factor is dependent on the fluence-to-dose conversion coefficients. These coefficients rely on the radiation weighting factor to link neutron fluence and the resulting equivalent dose. Al though the neutron energy spectra measured in the CANDU workplace cannot be approx imated by the calibration source’s neutron energy spectrum, the calibration factor remains constant—within acceptable limits—regardless of the neutron source used in calibration; for the specified calibration orientation and current radiation weighting factors. However, changing the value of the radiation weighting factors would result in changes to the cal ibration factor. OPG should evaluate the effect of any such modifications to determine whether a change to the calibration process or resulting calibration factor is warranted.
NEUTRON DOSIMETRY AT ONTARIO POWER GENERATION
Keywords: CANDU; Neutron dosimetry; Ontario Power Generation (OPG); SNOOPY; Canadian Nuclear Safety Commission (CNSC); Neutron radiation